DNA vaccine with discontinuous T‐cell epitope insertions into HSP65 scaffold as a potential means to improve immunogenicity of multi‐epitope Mycobacterium tuberculosis vaccine. (23rd September 2016) - Wu, Manli; Li, Min; Yue, Yan; Xu, Wei
ABSTRACT: DNA‐based vaccine is a promising candidate for immunization and induction of a T‐cell‐focused protective immune response against infectious pathogens such as Mycobacterium tuberculosis ( M. tb ). To induce multi‐functional T response against multi‐TB antigens, a multi‐epitope DNA vaccine and a 'protein backbone grafting' design method is adopted to graft five discontinuous T‐cell epitopes into HSP65 scaffold protein of M. tb for enhancement of epitope processing and immune presentation. A DNA plasmid with five T‐cell epitopes derived from ESAT‐6, Ag85B, MTB10.4, PPE25 and PE19 proteins of H37Rv strain of M. tb genetically inserted into HSP65 backbone was constructed and designated as pPES. After confirmation of its in vitro expression efficiency, pPES DNA was i.m. injected into C57BL/6 mice with four doses of 50 µg DNA followed by mycobacterial challenge 4 weeks after the final immunization. It was found that pPES DNA injection maintained the ability of HSP65 backbone to induce specific serum IgG. ELISPOT assay demonstrated that pPES epitope‐scaffold construct was significantly more potent to induce IFN‐γ + T response to five T‐cell epitope proteins than other DNA constructs (with epitopes alone or with epitope series connected to HSP65), especially in multi‐functional‐CD4 + T response. It also enhanced granzyme B + CTL and IL‐2 + CD8 + T response. Furthermore, significantly improved protection against Mycobacterium bovis BCG challenge was achieved by pPES injection compared to other DNA constructs. Taken together, HSP65 scaffold grafting strategy for multi‐epitope DNA vaccine represents a successful example of rational protein backbone engineering design and could prove useful in TB vaccine design.